Psoriasis in areas difficult to treat and biological therapy - Lis-Święty, Anna; Frątczak , Aleksandra (Dermatology Review/Przegląd Dermatologiczny, 2021)
Psoriasis often affects specific locations such as the nail apparatus, scalp, hands, feet, and genital areas. It usually coexists with severe plaque psoriasis. However in some cases only these areas may be affected, causing a significant deterioration of the patient’s quality of life, low self-esteem and depression. In the absence of effects of a topical treatment (glucocorticosteroids in monotherapy or combined with calcipotriol, keratolytic agents, phototherapy, calcineurin inhibitors) and standard systemic therapy (i.e., retinoids, methotrexate and cyclosporin), biological drugs are often used, even though the PASI score does not exceed 10. Interleukin-17 inhibitors and interleukin-23 inhibitors, are the most adequate biological drugs for isolated psoriasis in these special anatomic locations